Políticas sociais e questões ambientais - Moreira, Andrea Batista (2014)
The present study aimed to analyze the relationship between social issues and environmental issues. For this, it became necessary: to analyse the relationship that exists between identifying social policies and environmental conservation; analyze their contribution to the survival of workers and the unemployed. Regarding methodology, it is a bibliographic and documentary research, with readings about the topic made in books, magazines, scientific articles, as well as surveys, theses and dissertations related to the topics. We tried to analyze the possible relationship between the denial of rights that are guaranteed by law, which run precariously by social policies (welfare, education, health, housing, environmental, etc..). Throughout history, social exclusion and inequality manifested and were treated in various ways, but there was no significant change in the existing order. Even so, vindicated movements achieved some victories that would not be possible without the process of mobilization of the working classes as well as social movements. We observe that in the social rights era, the Brazilian Federal Constitution of 1988, was a milestone in the consolidation of these, mostly in the form that that Constitution was drafted with the participation of the civil society. However, there is a big gap between laws and their enforcement, because if they were to be implemented, we would not have a picture of chronic poverty - being necessary the existence of palliative measures such as minimum income programs - as well as disrespect for the environment. Finally, we discuss the progress and setbacks in the implementation of social policies and their implications.